2022
DOI: 10.1080/1478422x.2022.2058779
|View full text |Cite
|
Sign up to set email alerts
|

Impact of added Inconel and stainless steel on zirconium-based alloys for nuclear waste applications

Abstract: Three alloys were made to represent waste forms for ZIRLO® cladding and metallic fuel wastes by alloying ZIRLO® and a surrogate metallic fuel waste mixture with various amounts of Inconel 718, 304 stainless steel, trim chromium, and trim copper. The objective was to establish if metallic wastes that contain ZIRLO® can be manufactured into durable waste forms for geological repository. Specimens were metallurgically characterized and subjected to electrochemical tests to assess their corrosion resistance. Tests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“… 29 Corrosion resistance of SS 304L, Inconel 718, and trim chromium was studied under acidic and alkaline electrolytes conditions. 30 The microstructural characterization and potentiodynamic (PD) parameters of these alloys were evaluated. Surface analysis of the corroded alloys after potentiodynamic studies clearly revealed that the intermetallics dominated with iron metal and nickel and copper were found relatively low in the presence of Cl – solution.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… 29 Corrosion resistance of SS 304L, Inconel 718, and trim chromium was studied under acidic and alkaline electrolytes conditions. 30 The microstructural characterization and potentiodynamic (PD) parameters of these alloys were evaluated. Surface analysis of the corroded alloys after potentiodynamic studies clearly revealed that the intermetallics dominated with iron metal and nickel and copper were found relatively low in the presence of Cl – solution.…”
Section: Resultsmentioning
confidence: 99%
“…Surface analysis of the corroded alloys after potentiodynamic studies clearly revealed that the intermetallics dominated with iron metal and nickel and copper were found relatively low in the presence of Cl – solution. 30 Recently, long-term corrosion of multiphase alloy and oxide material were examined under geologic disposal conditions. 31 They confirmed that electrochemical impedance spectroscopy altered the electrical properties of the alloys surfaces and corrosion rates.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations